Ultra-long Distance Distributed Intrusion Detecting System Assisted With In-line Amplification - Macheng Lai; Kuan Peng; Yiyang Luo; Xiaolei Li; Yanpeng Li; Fan Ai; Deming Liu; Qizhen Sun (IEEE Photonics Journal)
An ultra-long distance distributed intrusion detecting system assisted with power amplification and sensitivity enhancement is proposed and demonstrated. First, through introducing multiple bidirectional amplifiers into the unbalanced Mach–Zehnder/Sagnac interferometer-based fiber sensing link, the sensing distance is remarkably extended, and second, the signal-to-noise ratio of this sensing system is significantly improved from less than 2 to 6–8 dB by coating the sensing fiber with organic silicone polymer. Furthermore, the high-order downtrend fitting function is adopted to implement the intrusion locating of ultralong distance sensing; the zero-padding fast Fourier transform algorithm and multiple-averaging method are jointly utilized for the improvement of the locating accuracy. Experimentally, a proof-of-concept distributed intrusion detecting system is constructed with the employment of bidirectional amplification. In particular, the ultra-long sensing distance up to 226.337 km is implemented, which is the reported longest distributed sensing system to the best of our knowledge.